(untitled) (International Journal of Engineering and Computer Science, 2017)
Securing your Computer/Laptop and its vital data is the most important concern for everybody in today’s life. We want to secure our device when we are not using it, or might be we are not in the proximity of it. Many a times, it happens that our device password is known by people close to us. They can use this password to login secretly, and steal/change some vital data. Hence, securing our systems, when we are not in its proximity is an important task. To do so, we have to have some lock on our system by which only we could be able to open it. A solution to this is to have additional password in order with the normal Windows password on login. This will be a one-time password and will change on every login. This will act as an additional protection for the system. Also, using the Bluetooth technology we will maintain the user authentication and communication to track the authenticated user.